The Macrophage Mannose Receptor Regulate Mannan-Induced Psoriasis, Psoriatic Arthritis, and Rheumatoid Arthritis-Like Disease Models - Hagert, Cecilia; Sareila, Outi; Kelkka, Tiina; Jalkanen, Sirpa; Holmdahl, Rikard (Frontiers in Immunology, 2018)
The injection of mannan into mice results in the development of a disease that closely mimics the human diseases psoriasis and psoriatic arthritis, while co-injection of mannan with antibodies against collagen type II leads to a chronic more rheumatoid-like arthritis. The critical event in all these diseases is mannan-mediated activation of macrophages, leading to more severe disease if the macrophages are deficient in Ncf1 and lack the capacity to make reactive oxygen species (ROS). In this study, we investigated the role of one of the receptors that binds mannan, the macrophage mannose receptor (MR, or CD206), a C-type lectin expressed on myeloid cells and lymphatic endothelial cells. Mice deficient in MR developed more severe mannan-induced psoriasis, psoriatic arthritis, and rheumatoid-like arthritis. Interestingly, the MR-mediated protection was partly lost in Ncf1-deficient mice and was associated with the expansion of M2 macrophages. These results suggest that MR protects against a pathogenic inflammatory macrophage response induced by mannan and associated with the production of ROS.